Digital Literacy among Bakery Industry Entrepreneurs: A Review based on the Triple Helix Model (International Journal of Creative Future and Heritage (TENIAT), 2025)
ABSTRACTThe application of digital literacy among bakery industry traders is increasingly important in the era of rapid digital transformation. However, the level of mastery and use of digital technology among small entrepreneurs is still low and unbalanced, especially in terms of strategic support from universities, industry and government. Therefore, this study was conducted to identify the role and significance of the relationship using the Triple Helix Model to understand the role of these three entities in strengthening the digital literacy of local bakery traders. The design of this study used a quantitative approach through a survey method using a questionnaire as the main instrument. Based on the Krejcie and Morgan Table, the recommended sample size for a population of 89 is 73 respondents. However, this study used 57 respondents based on the accessibility and willingness of participants to be involved, in addition to considering time and resource constraints. The questionnaire that was constructed consisted of four sections, namely demographic information (Section A), the role of the industry (Section B), the role of the university (Section C) and the role of the government (Section D). A five-point Likert scale was used to measure the perceptions of the respondents. Statistical analysis showed that there was a significant relationship between the role of industry and government (r=0.000, p
Keywords: Digital Literacy; Bakery Trader; Triple Helix Model; Role of university; Role of Industry; Role of government